Development of a dental handpiece angle correction device - Yoon Nam; Mi Young Eo; Soung Min Kim (BioMedical Engineering OnLine, 2018)
Abstract Background Preparation of a uniform angle of walls is essential for making an ideal convergence angle in fixed prosthodontics. We developed a de novo detachable angle-correction apparatus for dental handpiece drills that could help the ideal tooth preparation. Methods We utilized a gyro sensor to measure the angular velocities to calculate the slope of an object by integrating the values, acceleration sensor to calculate the slope of an object by measuring the acceleration relative to gravity, and Kalman filter algorithm. Converting the angulation of the handpiece body to its drill part could be performed by a specific matrix formulation set on two reference points (2° and 6°). A flexible printed circuit board was used to minimize the size of the device. For convergence angle investigation, 16 volunteers were divided randomly into two groups for performing tooth preparation on a mandibular first molar resin tooth. All abutments were scanned by a 3D scanner (D700®, 3Shape Co., Japan), the convergence angle and tooth axis deviation were analyzed by a CAD program (SolidWorks 2013®, Dassault Systems Co., USA) with statistical analysis by Wilcoxon signed-rank test (α = 0.05) using SPSS statistical software (Version 16.0, SPSS Inc.). Results This device successfully maintained the stable zero point (less than 1° deviation) at different angles (0°, 30°, 60°, 80°) for the first 30 min. In single tooth preparation, without this apparatus, the average bucco-lingual convergence angle was 20.26° (SD 7.85), and the average mesio–distal (MD) convergence angle was 17.88° (SD 7.64). However, the use of this apparatus improved the average BL convergence angle to 13.21° (SD 4.77) and the average MD convergence angle to 10.79° (SD 4.48). The angle correction device showed a statistically significant effect on reducing the convergence angle of both directions regardless of the order of the directions. Conclusions The angle correction device developed in this study is capable of guiding practitioners with high accuracy comparable to that of commercial navigation surgery. The volume of the angle correction device is much smaller than that of any other commercial navigation surgery system. This device is expected to be widely utilized in various fields of orofacial surgery.